ELEMENTARY SCHOOL STUDENT COOPERATION CHARACTER PROFILE IN SINGKAWANG CITY - Iip Istirahayu (Universitas Pendidikan Indonesia, 2023)
The character of cooperation is known as Gotong Royong which is the culture of the Indonesian nation, so it needs to be maintained and developed so that it remains a person who has a cooperative character. The purpose of this study was to measure the level of cooperative character of elementary school students in Singkawang City. The research method used was a quantitative survey in the form of a survey, conducted on elementary school students with a sample 322 of upper class students in 10 schools in a stratified manner. sampling. The results of the research on the cooperative character profile of elementary school (SD) students can be concluded to be in the medium category, meaning that students have good motive aspects. That is, each individual who interacts has certain motives and goals. Having a good emotional aspect, that is, each individual is driven by the same feelings in social interactions. Having a good interaction aspect, namely being able to relate to other individuals. Having leadership aspects, namely being able to lead groups. Has an external aspect, namely the interaction and sentiment from outside influences (external system). Has an internal aspect of the system, namely creating a common awareness and action that gives rise to an internal system. There are forty-seven other students in the high category, which have excellent cooperative characters, namely having stable motives and goals, being able to manage emotions well in interactions, being able to build interactions with other friends, having the ability to lead groups well. , able to influence the parks well, have awareness and act of cooperation very well. There are eighteen students in the low category, which means they have a fairly good cooperative character in the motive aspect, emotional aspect, interaction aspect, leadership aspect, external aspect, and internal aspect.